The fate of the Soviet Bloc's military alliance reform, adaptation, and collapse of the Warsaw Pact, 1985-1991 - Kramer, Mark R. (Cambridge University Press, 2025)
When Mikhail Gorbachev became the leader of the Soviet Union in 1985, the Warsaw Pact was a robust military alliance. It was capable of waging a large-scale war in Europe and was an instrument of Soviet hegemony in Eastern Europe, keeping orthodox Communist regimes in power. The alliance over the years had also become an effective mechanism of political coordination and consultation. In April 1985, the Warsaw Pact leaders met in Warsaw and renewed the Pact for another thirty years. Yet only six years later, the alliance was disbanded, having been rendered obsolete by the political transformation of Eastern Europe in 1989-1990. This monograph recounts what happened to the Warsaw Pact during its final years and explains why the organization ceased to exist in 1991